Enhancing dermatological diagnosis for differentiating actinic from seborrheic keratosis using deep learning model - Ren, Ying-Ying; Mei, Li-Hong; Liu, Xiang-Dong; Quan, Zhe; Yang, Gao (Frontiers in Medicine, 2025)
BackgroundDifferentiating Actinic keratosis (AK) from Seborrheic keratosis (SK) can be challenging for dermatologists due to their visual similarities. This multi-center prospective study aims to investigate the efficacy of deep learning (DL) model in assisting dermatologists in accurately classifying AK from SK lesions.MethodsA contrastive language-image pre-training (CLIP) model with ViT-B/16 architecture was trained on an dataset of 2,307 patients and validated in three separate datasets of 386 (from Center A), 196 patients (from Center B and C) and 215 patients (from DermNet). Two dermatologists classified the lesions separately. Then they were showed the model’s predictions and were requested to reclassify the results if needed. Area under the receiver operating characteristic (ROC) curve (AUC) was used to evaluate the diagnostic performances of the DL model and the dermatologists before and after reclassification. The change in the dermatologists’ classification decisions was also analyzed by net reclassification index (NRI) and total integrated discrimination index (IDI).ResultsThe model’s diagnostic performance in the training cohort and validation cohort 1, 2 and 3 showed an AUC of 0.85, 0.89, 0.84, and 0.89. For dermatologist 1, the diagnostic performance improved from 0.77 to 0.80 in the test cohort with NRI and IDI of 0.10 (p = 0.006) and 0.14 (p < 0.001). For dermatologist 2, the diagnostic performance increased from 0.69 to 0.79 with NRI and IDI of 0.19 (p < 0.001) and 0.27 (p < 0.001).ConclusionThe DL model significantly improves dermatologists’ accuracy in differentiating AK from SK, especially for less experienced ones. The DL model has the potential to reduce diagnostic subjectivity, aid early detection of precancerous lesions, and transform dermatological diagnostic and therapeutic practices.